MANAJEMEN KOMPENSASI DAN REWARD DALAM MENINGKATKAN KINERJA PEGAWAI - Afriza; Abu Bakar (Al-mujahidah, 2024)
Providing education is important in any country in the world. Educational institutions as a forum where the educational process takes place have a strategic role in making educational activities a success. Through education, humans are forged and formed into individuals who have competitive abilities in the midst of society. Teachers as drivers of education have a complex task in creating quality education. Thus, teachers should receive special attention from various parties, especially the government. This attention must at least be realized in the form of providing compensation and rewards to teachers. Because compensation and rewards will be able to build work motivation so that quality education will be realized. This article will describe compensation and rewards in improving employee performance. The study method in this paper is using the library research method. Library research is a research method that uses literature and documents to reveal the problem that is the research topic. From the results of the study, it was found that compensation and rewards have a very big impact on teachers. Rewards can boost teacher performance and build teacher trust in institutional leaders. Compensation and rewards are a form of appreciation for teachers for their services in educating, guiding and developing students